Ectopic Expression of CsKCS6 From Navel Orange Promotes the Production of Very-Long-Chain Fatty Acids (VLCFAs) and Increases the Abiotic Stress Tolerance of Arabidopsis thaliana - Guo, Wenfang; Wu, Qi; Yang, Li; Hu, Wei; Liu, Dechun; Liu, Yong (Frontiers in Plant Science, 2020)
Cuticular wax is closely related to plant resistance to abiotic stress. 3-Ketoacyl-CoA synthase (KCS) catalyses the biosynthesis of very-long-chain fatty acid (VLCFA) wax precursors. In this study, a novel KCS family gene was isolated from Newhall navel orange and subsequently named CsKCS6. The CsKCS6 protein has two main domains that belong to the thiolase-like superfamily, the FAE1-CUT1-RppA and ACP_syn_III_C domains, which exist at amino acid positions 80-368 and 384-466, respectively. CsKCS6 was expressed in all tissues, with the highest expression detected in the stigma; in addition, the transcription of CsKCS6 was changed in response to drought stress, salt stress and abscisic acid (ABA) treatment. Heterologous expression of CsKCS6 in Arabidopsis significantly increased the amount of VLCFAs in the cuticular wax on the stems and leaves, but there were no significant changes in total wax content. Compared with that of the wild-type (WT) plants, the leaf permeability of the transgenic plants was lower. Further research showed that, compared with the WT plants, the transgenic lines experienced less water loss and ion leakage after dehydration stress, displayed increased survival under drought stress treatment and presented significantly longer root lengths and survival under salt stress treatment. Our results indicate that CsKCS6 not only plays an important role in the synthesis of fatty acid precursors involved in wax synthesis but also enhances the tolerance of transgenic Arabidopsis plants to abiotic stress. Thus, the identification of CsKSC6 could help to increase the abiotic stress tolerance of Citrus in future breeding programmes.